2020
DOI: 10.1038/s41396-020-00789-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct interactions with commensal streptococci modify intercellular communication behaviors of Streptococcus mutans

Abstract: The formation of dental caries is a complex process that ultimately leads to damage of the tooth enamel from acids produced by microbes in attached biofilms. The bacterial interactions occurring within these biofilms between cariogenic bacteria, such as the mutans streptococci, and health-associated commensal streptococci, are thought to be critical determinants of health and disease. To better understand these interactions, a Streptococcus mutans reporter strain that actively monitors cell–cell communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
(100 reference statements)
4
18
0
Order By: Relevance
“…In addition to the host‐driven mechanisms of metal sequestration, bacteria in polymicrobial biofilms such as dental plaque must also compete with the other oral residents for nutrients. Interestingly, a recent study showed that transcription of the S. mutans adcA and adcB genes was induced (about six‐ and threefold, respectively) when S. mutans was co‐cultured with Streptococcus A12, a health‐associated peroxigenic oral streptococcus (Kaspar et al., 2020). It should be noted that, in principle, peroxigenic streptococci are better equipped to scavenge zinc than S. mutans due to the concerted effort of AdcAII and Pht proteins in addition to the AdcABC system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the host‐driven mechanisms of metal sequestration, bacteria in polymicrobial biofilms such as dental plaque must also compete with the other oral residents for nutrients. Interestingly, a recent study showed that transcription of the S. mutans adcA and adcB genes was induced (about six‐ and threefold, respectively) when S. mutans was co‐cultured with Streptococcus A12, a health‐associated peroxigenic oral streptococcus (Kaspar et al., 2020). It should be noted that, in principle, peroxigenic streptococci are better equipped to scavenge zinc than S. mutans due to the concerted effort of AdcAII and Pht proteins in addition to the AdcABC system.…”
Section: Discussionmentioning
confidence: 99%
“…mutans adcA and adcB genes was induced (about six-and threefold, respectively) when S. mutans was co-cultured with Streptococcus A12, a health-associated peroxigenic oral streptococcus (Kaspar et al, 2020). It should be noted that, in principle, peroxigenic streptococci are better equipped to scavenge zinc than S. mutans due to the concerted effort of AdcAII and Pht proteins in addition to the AdcABC system.…”
Section: Mutansmentioning
confidence: 99%
“…In addition to the host-driven mechanisms of metal sequestration, bacteria in polymicrobial biofilms such as dental plaque must also compete with the other oral residents for nutrients. Interestingly, a recent study showed that transcription of the S. mutans adcA and adcB genes was induced (about 6-and 3-fold, respectively) when S. mutans was co-cultured with Streptococcus A12, a health-associated peroxigenic oral streptococci (Kaspar, Lee, Richard, Walker, & Burne, 2020). It should be noted that, in principle, peroxigenic streptococci are better equipped to scavenge zinc than S. mutans due to the concerted effort of AdcAII and Pht proteins in addition to the AdcABC system.…”
Section: Discussionmentioning
confidence: 99%
“…Finally we note that the oral biofilm is a complex multispecies community in which S. mutans must compete with a number of commensal species ( Bowen et al, 2018 ). These interactions can lead to highly localized inhibitory effects on competence behavior ( Kaspar et al, 2020 ). Therefore, although the present work shows that the physical properties of the single-species biofilm do not themselves impose heterogeneity in competence behavior, localized interactions with commensal species may quite possibly impose spatial heterogeneity onto competence.…”
Section: Discussionmentioning
confidence: 99%